Financing Small and Medium-Size Enterprises with Factoring: Global Growth and its Potential in Eastern Europe - Bakker, Marie H. R.; Klapper, Leora; Udell, Gregory F. (Warsaw: World Bank, 2013)
Factoring is a form of asset-based finance where the credit is extended based on the value of the borrower's accounts receivable. In recent years factoring has experienced phenomenal growth and has become an important source of financing-especially short-term working capital-for small and medium-size enterprises and corporations, reaching a worldwide volume of 760 billion euro in 2003. Although the importance of factoring varies considerably around the world, it occurs in most countries and is growing especially quickly in many developing countries. The authors explore the advantages of factoring over other types of lending for firms in developing economies, and discuss the informational, legal, tax, and regulatory barriers to its growth. They also examine the role of factoring in the eight Eastern European countries that became EU members on May 1, 2004-the Czech Republic, Estonia, Hungary, Latvia, Lithuania, Poland, the Slovak Republic, and Slovenia, referred to as the EU 8. The authors conclude that factoring offers key advantages over other lending products and is likely to become more important in these countries, and suggest policies to accelerate its development.